Making Hospitals Governable: Performativity and Institutional Work in Ranking Practices. Issue 4 (April 2019) - Wallenburg, Iris; Quartz, Julia; Bal, Roland
Rankings have become ubiquitous in public service settings. Although there are high hopes that comparative analysis leads to improved processes and outcomes, there is also a growing criticism of rankings as creating perverse effects. In this article, we analyze how public service governance is affected by rankings with a special focus on how, in what ways, and to what extent organizations are made into governable entities as a response to rankings. The article is based on a detailed ethnographic study in three Dutch hospitals, using insights from actor–network theory and institutional work, combining the concepts of performativity and institutional work.